Management Science and Research in Great Britain - Wilkins, Leslie T. (Management Science, 1961)
This paper is divided into three parts. In the first part, the present stage of development of management science in the United Kingdom is briefly discussed; in the second part are given a few “case histories,” stressing the methodology; the third part discusses a few recent features of management science in the United Kingdom which seem to be interesting.